Unintended effects of a family-friendly law in a segmented labor market - Daniel Fernández-Kranz; Nuria Rodriguez-Planas (Institute for the Study of Labor (IZA), 2011)
Family-friendly laws may backfire if not all workers with access to the policies use them. Because these policies are costly to the employer, hiring practices may consequently be affected at the detriment of the at-risk population who may end up accessing the policy. We exploit a 1999 Spanish law that granted all workers with children under 7 years the right to work part-time. Most importantly, the law declared a layoff invalid if the worker had previously asked for a work-week reduction due to family responsibilities. Using a difference-in-differences (DD) methodology, we first find evidence that the law increased part-time work among eligible mothers with a permanent contract, but had no effect on eligible fathers or mothers with a temporary contract. This effect is driven by the less-educated women. Then, using both a DD and a DDD approach, we analyze the effects of the law among the at-risk population, i.e., childbearing-aged women with no children under 7. We find that this policy led to the unintended effect of decreasing the likelihood of being employed with a permanent contract among the at-risk high-school graduate women (relative to their male counterpart), while increasing their relative likelihood of having a fixed-term contract job. These findings suggest that, after the law, employers preferred hiring childbearing-aged men under permanent contracts (offering fixed-term contracts to childbearing-aged women).
urn:nbn:de:101:1-201105306346
Keywords: J21; J68; J78; 330; temporary employment; flexible work arrangement laws; European unemployment